Peripheral osteoma in the ramus of mandible: report of case - Alves, Nilton [UNESP]; Oliveira, Reinaldo de; Deana, Naira Figueiredo; Freitas, Nelma Maria de (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
The osteomas are benign rare neoplasms, generally asymptomatic which are characterized by the proliferation of a compact or spongy bone. When they are situated in the maxillofacial area, they affect mainly the mandible, the frontal bone and the paranasal sinus. We have described the case of a female caucasian patient who presented an increased volume in the posterior region of the oral vestibule on the left side. During the clinical examination an oral lesion was observed in the region of the left ramus of mandible. This lesion was motionless, consistent, and painless when palpated. In the image obtained from the computed tomography cone–beam (CBCT), we could observe an hyperdense, cylindrical region, with well defined borders, located in the medial surface of the left ramus of mandible, right below the mandibular notch. Based on clinical data and in the obtained images, we could confirm the presence of the peripheral osteoma in the left side of the ramus of mandible region.

Los osteomas son neoplasias benignas, raras, en la mayoría de los casos asintomáticas, que se constan principalmente de hueso maduro, compacto o esponjoso. De acuerdo a su ubicación en la región maxilofacial, la mandibula, el hueso frontal y los senos paranasales son preferentemente afectados. Describimos un caso de un paciente, sexo femenino, caucásica, que presentaba un aumento de volumen en la región posterior del vestíbulo oral en el lado izquierdo. Al examen clínico se observó una lesión inmóvil, consistente e indolora a la palpación. En la imagen obtenida a través del tomógrafo computado volumétrico Cone Beam (CBCT), se observó una región híperdensa, cilíndrica, con márgenes marcados, ubicada en la cara medial de la rama mandibular izquierda, inferior a la escotadura mandibular. Con base en los datos clínicos y las imágenes obtenidas se puede concluir la presencia de osteoma periférico en región de rama mandibular izquierda.
Osteoma periférico en la rama mandibular: reporte de caso
Keywords: Peripheral osteoma; Computed tomography cone–beam; Ramus of mandible; Osteoma periférico; Tomografía computada volumétrica Cone-Beam; Rama mandibular